2022
DOI: 10.4081/reumatismo.2022.1420
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of ANA/DFS70 autoantibodies in Colombian patients with undifferentiated connective tissue disease

Abstract: The objective was to describe the clinical characteristics and the frequency of the ANA/DFS70 autoantibodies in patients affected by undifferentiated connective tissue disease (UCTD) in a tertiary hospital in Colombia. This descriptive cross-sectional study enrolled patients who fulfilled the classification criteria for UCTD. ANAHEp- 2 test and the modified assay for ANA/DFS70 autoantibodies were performed through the indirect immunofluorescence technique. Erythrocyte sedimentation rate, C-reactive protein, rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Anti‐DFS70 antibodies are thought to have this function. 34 Infantino et al 33 evaluated 91 patients diagnosed with UCTD, documenting a high prevalence of anti‐DFS70 antibodies in this study group (13.3%). Given that the presence of these antibodies is not typical for CTDs, anti‐DFS70 appears to be a reliable marker for UCTD and indicates a low risk of specific CTD developing.…”
Section: Undifferentiated Connective Tissue Disease (Uctd)mentioning
confidence: 69%
See 3 more Smart Citations
“…Anti‐DFS70 antibodies are thought to have this function. 34 Infantino et al 33 evaluated 91 patients diagnosed with UCTD, documenting a high prevalence of anti‐DFS70 antibodies in this study group (13.3%). Given that the presence of these antibodies is not typical for CTDs, anti‐DFS70 appears to be a reliable marker for UCTD and indicates a low risk of specific CTD developing.…”
Section: Undifferentiated Connective Tissue Disease (Uctd)mentioning
confidence: 69%
“…Therefore the search for serological markers that will help exclude the diagnosis of UCTD with a high risk of progression to CTD has been undertaken. Anti‐DFS70 antibodies are thought to have this function 34 . Infantino et al 33 evaluated 91 patients diagnosed with UCTD, documenting a high prevalence of anti‐DFS70 antibodies in this study group (13.3%).…”
Section: Undifferentiated Connective Tissue Disease (Uctd)mentioning
confidence: 72%
See 2 more Smart Citations
“…Infantino's study concluded that patients with UCTD who are positive for anti-DFS70 antibodies are less likely to progress to CTD based on the signi cantly higher detection rate of anti-DFS70 antibodies in patients with UCTD (13.3%, 12/91) compared to CTD (2.6%, 10/384) [15]. Another article supported this conclusion, reporting only 1 in 5 UCTD patients with anti-DFS70 differentiated into SLE in 5 years [39]. However, due to the paucity of literature and data on related studies, the protective effect of anti-DFS70 in UCTD patients remains to be con rmed by multi-center, inter-regional and inter-ethnic long-term follow-up studies.…”
Section: Discussionmentioning
confidence: 97%